Compare of Clustering School Operational Aid Using Fuzzy Cluster Means and Fuzzy Geographically Weighted Clustering Method - Wasono, Rochdi; Ismunarti, Dwi Haryo (Proceeding International Conference on Science and Engineering, 2020)
The use of appropriate Cluster method will support the distribution of School Operational Aid (BOS) fund. Clustering is needed to classify the amount of School Operational Aid (BOS) funds with other influential variables with the aim as the consideration in making policy on the distribution and amount of School Operational Aid funds. Compare of method Fuzzy Cluster Means and Fuzzy Geographically Weighted Clustering were used. The variables used in this study were the School Operational Aid (BOS) funds, total coaching costs, and total regency/city management costs in Central Java Province. The best result of the clustering process was Fuzzy Geographically Weighted Clustering use cluster 3.